Leaf litter decay process and the growth performance of Aedes albopictus larvae (Diptera: Culicidae) - Dieng, Hamady; Mwandawiro, Charles; Boots, Michael; Morales, Ronald; Satho, Tomomitsu; Tuno, Nobuko; Tsuda, Yoshio; Takagi, Masahiro (Wiley Online Library, 2002)
Larvae of the mosquito Ae. albopictus typically develop in small aquatic sites such as tree holes and artificial containers. Organic detritus, in particular decaying leaves, is therefore their major carbon source. Here we demonstrate the importance of leaf characteristics, and in particular their rates of decay, in determining the development and survivorship of larvae. We compared the effects of a rapidly decaying leaf, the maple Acer buergerianum (Angiospermae: Aceraceae) and a slowly decaying leaf, the camphor Cinnamomum japonicum (Angiospermae: Lauraceae), on the larval development of Ae. albopictus at different larval densities in laboratory microcosms. Overall, the maple leaves provided a better substrate and the observed growth patterns could be explained on the basis of a difference in nutritive and chemical contents of the two leaf types. At the highest population density, the duration of the larval period was much shorter in maple litter microcosms. Larval mortality gradually increased with population density in the camphor treatment. In contrast in the rapidly decaying leaf litter microcosms, mortality remained low even as densities increased. Mean pupal size was greater in the individuals fed on the rapidly decaying leaf litter as well as at lower density. Size is likely to be correlated with fitness in the field. In general, rapidly decaying leaf litter will favor mosquito growth resulting in quicker development and higher population sizes. This work emphasizes the importance of the local environment on the development of vector mosquitoes and has important implications for control.